PRODUCT QUALITY AND PROMOTION RELATION ANALYSIS ON PURCHASING DECISION AT PT. SEJAHTERA BUANA TRADA (CASE STUDY OF SUZUKI ERTIGA) - Imam Yunianto (JEES: Journal of Economic Empowerment Strategy, 2018)
This research was conducted at Car Dealer PT. Sejahtera Buana Trada Puri Indah branch with case study Suzuki Ertiga which at the time of research is selling well. In this study, researchers wanted to test whether there is a significant relationship between Product Quality with Purchase Decision. The purpose of this study knowing whether it is true that a good quality product from a car can make car sales increase, knowing whether a good promotion can increase sales and knowing if the product quality and promotion done together can increase sales. The research method use is quantitative. The sample of this research are all buyers of Suzuki Ertiga car that buy to Suzuki Sejahtera Buana Trada car dealership during the third quartet of 2013, which is between July until September 2012. Is there also a significant relationship between Promotion on Purchase Decision. As well as a significant relationship between Product Quality and Promotion together with Purchase Decision.